Autoimmune Diseases and Gut Symbionts: The Unpopular Liaison - Nor Effa, Zulkafli; Phang, Shou Jin; Hajar Fauzan, Ahmad (Universiti Putra Malaysia, 2019)
In the past few years, compelling data have shown the potential crosstalk between dysbiosis of gut microbiota (GM) and impairment of systemic immune system. Since then, ideas on how GM partake in autoimmune conditions was put forward. Although genetic variability have been proven to contribute towards the pathogenesis of autoimmune conditions, epigenetics control have gained interest among researchers. Current review highlights the crosstalk between autoimmune conditions and GM and its potential regulatory mechanisms. Convincing data from existing literature help in paving ways for more well-defined species in the future studies. The studies should focus on identifying the distinct species involve in different types of autoimmune diseases and their definitive role in autoimmunity. Ultimately, these data can be used for the advancement of therapeutic approach in personalized medicine.